Photovoltaic and impedance spectroscopy characterization of single-junction a-Si:H p–i–n solar cells deposited by simple shadow masking techniques using PECVD - Kawtar Belrhiti Alaoui (AIP Advances, 2020)
Hydrogenated amorphous silicon p–i–n solar cells with a 1 × 1 cm2 active surface area were fabricated using shadow masks on the 20 × 20 cm2 glass substrate coated with a fluorine-doped tin oxide film. The intrinsic, n-type hydrogenated amorphous silicon (a-Si:H), and p-type a-SiC:H thin films were deposited using plasma-enhanced chemical vapor deposition at 13.56 MHz plasma excitation frequency and on 20 × 20 cm2 and SnO2:F covered glass substrates. Low rf-power densities (less than 0.1 W/cm2) and substrate temperatures (less than 190 °C) were used for this purpose. Raman spectra of the films are dominated by a broad peak around 480 cm−1 that is the characteristic of the amorphous silicon network for all the three types of films. Scanning electron microscopy measurements revealed that the surface of the a-Si:H films deposited on SnO2:F-coated glass substrates (Asahi-VU) replicates the texture of the SnO2:F film. Spectroscopic ellipsometry spectra were analyzed with the Tauc–Lorentz dispersion model, and the results revealed that the optical gap of the intrinsic a-Si:H films is on the order of 1.7 eV, while that of the a-SiC:H is on the order of 1.8 eV. These results were further confirmed by optical transmission measurements. The highest efficiency obtained for solar cells prepared with shadow masking under our condition is on the order of 8.83% with a Voc of 0.856 V, a short circuit current density of 15.6 mA/cm2, and a fill factor of 66.07%. The obtained efficiency is slightly lower than the record efficiency obtained in this family of cells (10.3%) prepared by laser scribing because the low short-circuit current slightly lowers the fill factor. Impedance spectroscopy measurements were performed on the cells in the dark in the frequency range of 1 kHz–100 kHz. The analysis of impedance either in the Nyquist diagram or in the Bode diagram suggests a lumped circuit consisting of resistance Rs in series with a parallel combination of resistance Rp and capacitance Cp that account for the p–i–n structure. The value of Rp changed with the applied DC bias. The value of the series resistance agrees with the value obtained from the current–voltage characteristics of the cell.